Manfaat Filsafat bagi Pengembangan Kurikulum Manajemen Pendidikan Islam - Suheri, Suheri; Sujanto, Bedjo; Aisyatunnadiya, Siti (Lembaga Intelektual Muda (LIM) Maluku, 2026)
Philosophy plays a strategic role in the development of the curriculum of Islamic education management, as it provides a conceptual, value-based, and directional foundation for educational goals. This study aims to examine the benefits of philosophy in developing the curriculum of Islamic education management, particularly in strengthening the integration of spiritual, intellectual, and moral dimensions. This research employs a qualitative descriptive approach using a library research method, analyzing books on educational philosophy, Islamic philosophy, as well as relevant scholarly articles and journals. The findings indicate that philosophy, through the branches of ontology, epistemology, and axiology, plays a significant role in formulating the objectives, content, methods, and evaluation of the Islamic education curriculum. Various philosophical schools such as idealism, realism, pragmatism, and existentialism contribute to shaping a curriculum oriented toward the formation of insan kamil (the complete human being). Furthermore, the integration of bayani, irfani, and burhani epistemologies enriches curriculum development, making it more holistic and contextual. With a strong philosophical foundation, the curriculum of Islamic education management functions not merely as a means of knowledge transmission, but also as an instrument for character building, moral development, and social responsibility among learners.